Pemanfaatan Sampah Botol Plastik Bekas Sebagai Media Tanam (Pot) Pada Masyarakat Di RT 17 Kel. Pematang Gubernur - Wulandari, Melsa; Bela, Sinta; Augusta, Bella; Fira, Tiara Elma; Fitriani, Asty Eka; Putra, Iswidana Utama; Wahyudi, Yusuf; Irwanto, Tito (LPPM Universitas Dehasen Bengkulu, 2025)
Plastic waste is a major problem in Indonesia that contributes to environmental damage. This is due to the increasing demand for plastic in line with population growth and the lack of public awareness regarding the reuse of plastic waste. Plastic is indeed one of the biggest 'enemies' of the environment, with used beverage bottles being one of them. As is known, plastic has a negative impact on the environment because plastic is difficult to decompose by the soil even after being buried for years. One simple way that can be implemented in elementary schools to raise students' awareness of the environment is by using used plastic bottles as planting media. This activity aims to raise public awareness about reducing household waste. In addition, another goal is to utilize household waste for something more beneficial, in this case, as a planting medium. This method is carried out through counseling and the distribution of leaflets. The implementation of community service activities related to the management of inorganic household waste into planting media has been carried out well and smoothly. The understanding of the community in RT 17 Pematang Gubernur regarding the management of inorganic waste as a planting medium has increased.